PENGARUH KEGIATAN MENGGUNTING POLA GAMBAR GEOMETRIS TERHADAP KEMAMPUAN MOTORIK HALUS ANAK - Rohania; Nugraha, Anggi Purwa; Mulyono, Nono (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
In early childhood, understanding information would take place very quickly, therefore at this time early childhood is going to do a lot of imitation. So that, it is important to pay attention to enhance his/her fine motor skill sustainably. There are several activities that can be done to train fine motor skills in early childhood including geometric pattern cutting activities. This study aims at determining how the effect of geometric pattern cutting activities on early childhood’s fine motor skill of group B at RA Sabilissalam Baregbeg Ciamis. This study used quantitative method under pre-experiment through one-group pretest-posttest design. The sampling technique used was a saturated sample of 16 students. The processing technique was carried out using SPSS. The results of this study showed that the pretest indicated 12.5% of early childhood which is categorized underveloped (BB) and 87.5% of early childhood which is categorized developing category (MB). After the use of cutting activities, the posttest results showed an increase with 68.75% of early childhood which is categorized developing as expected (BSH) and 31.25% of early childhood which is categorized developing very well (BSB). Based on the results of the Wilcoxon test, the value of 0.000 <0.05 means that H1 is accepted and H0 is rejected. Then, it is concluded that the use of geometric pattern cutting activities has a significant effect on early childhood's learning at RA Sabilissalam Baregbeg Ciamis.